Factor analysis of teacher ratings for the Lithuanian translated behavioral and emotional rating scale - Lambert, Matthew C.; Nordness, Philip D.; Epstein, Michael H. (Social Welfare: Interdisciplinary Approach, 2014)
Internationally there has been increased recognition of the value of strength based assessment in educational and mental health service delivery. While there are a number of informal methods for determining a child’s strengths and assets, there are few standardized strength based assessments available for international use. In this study the teacher version of the Behavioral and Emotional Rating Scale-Second Edition (BERS-2) was translated into Lithuanian to determine its factor structure for use in Lithuania. The results suggest that the Lithuanian BERS-2 can be a useful strength based assessment for teachers and schools in Lithuania.
Keywords: strength-based assessment; assessment; Lithuania; education; behavior